Water quality pattern recognition of the Muda River Basin, Malaysia - Azhar, Shah Christirani (2017)
Muda River Basin (MRB) in the state of Kedah, Malaysia with the range values of Water Quality Index (WQI) were between 55.8 and 91.0 during the period 1998-2013. The wide variations in water quality (WQ) indicate that the MRB is affected by various sources. Agricultural-related cover approximately 55% of the total area of the MRB. Meanwhile, about 35% of the catchment area is still covered by forests. Therefore, agriculture, logging activities, and agro-based industries are the main human activities in the area which contributes to water pollution. While, the presence of point sources such as factories may cause river water quality at the same level degraded differently in the same catchment. Therefore, there is a growing interest to determine the sources of pollution and land use classes responsible for this deteriorated WQ and determining how the desired WQ can be secured on a sustainable basis.